Changes in Population Age-Structure Obscure the Temperature-Size Rule in Marine Cyanobacteria - Palacio, Antonio S.; Cabello, Ana María; García, Francisca C.; Labban, Abbrar; Morán, Xosé Anxelu G.; Garczarek, Laurence; Alonso-Sáez, Laura; López-Urrutia, Ángel (Frontiers in Microbiology, 2020)
The temperature-size Rule (TSR) states that there is a negative relationship between ambient temperature and body size. This rule has been independently evaluated for different phases of the life cycle in multicellular eukaryotes, but mostly for the average population in unicellular organisms. We acclimated two model marine cyanobacterial strains (Prochlorococcus marinus MIT9301 and Synechococcus sp. RS9907) to a gradient of temperatures and measured the changes in population age-structure and cell size along their division cycle. Both strains displayed temperature-dependent diel changes in cell size, and as a result, the relationship between temperature and average cell size varied along the day. We computed the mean cell size of new-born cells in order to test the prediction of the TSR on a single-growth stage. Cell size of new-born cells followed the predicted negative response to temperature. Our work may help reconcile previous inconsistent results when testing the TSR on unicellular organisms.